The European Joint Research Project UHDpulse – Metrology for advanced radiotherapy using particle beams with ultra-high pulse dose rates. (December 2020) - Schüller, Andreas; Heinrich, Sophie; Fouillade, Charles; Subiel, Anna; De Marzi, Ludovic; Romano, Francesco; Peier, Peter; Trachsel, Maria; Fleta, Celeste; Kranzer, Rafael; Caresana, Marco; Salvador, Samuel; et al.
Highlights: Ultra-high dose rate reduces adverse side effects in radiotherapy (FLASH effect). Studies and implementation in practice requires accurate dose measurements. An European joint research project was started to develop a measurement framework. Tools for dosimetry of ultra-high pulse dose rate beams will be provided. Abstract: UHDpulse – Metrology for advanced radiotherapy using particle beams with ultra-high pulse dose rates is a recently started European Joint Research Project with the aim to develop and improve dosimetry standards for FLASH radiotherapy, very high energy electron (VHEE) radiotherapy and laser-driven medical accelerators. This paper gives a short overview about the current state of developments of radiotherapy with FLASH electrons and protons, very high energy electrons as well as laser-driven particles and the related challenges in dosimetry due to the ultra-high dose rate during the short radiation pulses. We summarize the objectives and plans of the UHDpulse project and present the 16 participating partners.